Rare association of thermal burns of the knee and ankle with wounds of the patellar and achilles tendons - Laurent Désiré Ndzié Essomba; Téredjou Fatou Sanogo; Abdoul Kadri Moussa (Elsevier, 2023)
Contact burns involving the joints of the lower limbs are rare. When these burns are of the fourth degree, their treatment becomes a real challenge because they can damage important anatomical elements in statics and locomotion such as muscles, tendons, and bones. The functional prognosis of the lower limbs can be seriously compromised. We report the case of a steel worker, victim of a work accident that caused burns and deep wounds to the knee and contralateral ankle, with section of the patellar and Achilles tendons. Immediate surgical treatment with debridement of the burned and severed tissues and direct suture of the injured tendons, combined with a long period of rehabilitation, allowed the patient to return to his workstation.